POSTURAL CONTROL OF STUDENTS OF DIFFERENT BODY TYPES - Matiichuk, V. I.; Grygus, I. M.; Kashuba, V. O. (Rehabilitation and Recreation, 2024)
Introduction. Numerous sensory signals from the visual, somatosensory, and vestibular systems are used to control postural control. It is well known that to maintain postural stability, the central nervous system keeps the overall center of mass of the body within the boundaries of the supporting surface. The postural control of people with different body types has been studied in detail in static conditions, but this problem has not yet been investigated in steady-state conditions. The purpose of the study is to study the features of statodynamic stability of female students of different body types. Research methods: theoretical analysis and generalization of literature sources, pedagogical observation, anthropometric examination. The diagnostic and training complex “SportKat 650 TS” on the basis of a moving platform, a pedagogical experiment, and methods of mathematical statistics were used to determine the statodynamic stability of the students’ body. The study established the following stratification of 121 female students involved in the study, taking into account their inherent body type: 64 people have mesomorphic, 35 people – ectomorphic, 22 people – endomorphic somatotypes. The data obtained during the experiment reveal the tendency of the subjects (representatives of all experimental groups) to significant body vibrations in the sagittal plane, which emphasizes the difficulty of the latter in maintaining the desired body posture, i.e., the inability to minimize body vibrations on a moving support. Based on the analysis of the results of tests for performing motor tasks with more active body movements, such as the “Dynamic Test – Clockwise Movement” and the “Dynamic Test – Counterclockwise Movement”, girls aged 17–18 years who participated in the experiment had certain difficulties, including the inability to clearly display or maximize the result of the movement set by the Sport Kat 650 TS software. Conclusions. In general, postural stability can be considered as its ability to be maintained and remain qualitatively unchanged in response to interventions or fluctuations (including postural fluctuations) in control. Control over the state of statodynamic stability of the body is a very important and basic requirement in everyday life. Controlling the body’s statodynamic stability requires visual and vestibular influences, as well as proprioceptive and tactile somatosensory influences, to control the muscles that regulate posture throughout the body, especially in the lower extremities and trunk. Performing test exercises on the diagnostic and training complex “Sport Kat 650TS” made it possible to establish the absence of specific differences that make up obvious patterns that reflect the peculiarities of statodynamic stability of girls aged 17–18 years of different body types.